A high-filling and high-thixotropic AlSi12La0.05 solder paste and preparation method thereof
By using high-filled high-thixotropic AlSi12La0.05 solder paste in solder paste soldering of aluminum and its alloys, a hydrogen bond network is formed by using specific microsphere particle size distribution and solvent compatibility, the problems of excessively fast settlement rate and low filling rate of solder paste are solved, and efficient welding performance and construction performance are achieved.
Patent Information
- Application Number
- CN202510038746.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-01
AI Technical Summary
The existing solder paste used for brazing of aluminum and its alloys has problems of too fast settling rate and low filling rate, resulting in interruption of processing, waste of materials and increased process costs.
High-filled high-thixotropic AlSi12La0.05 solder paste is used, which consists of AlSi12La0.05 microspheres, polymethyl methacrylate microspheres, 1,3-propylene glycol, 1,2-butanediol, octylphenol polyoxyethylene ether and methyl nylonate. The hydrogen bond network is formed through specific particle size distribution and solvent compatibility to improve thixotropy and filling rate.
A high fill rate of 94.5 wt% and a thixotropic index greater than 11 were achieved, which reduced the viscosity of the solder paste, improved the construction performance, avoided settlement problems, and improved the quality of the weld.
Abstract
Description
Technical Field
[0001] The invention relates to the field of new materials, and in particular to a high-filling and high-thixotropic AlSi12La0.05 solder paste and a preparation method thereof. Background Art
[0002] Aluminum and its alloys are one of the important structural materials. Their specific gravity is only one-third of that of steel and their specific strength is high. At the same time, aluminum has good electrical and thermal conductivity, excellent processing, surface treatment and corrosion resistance. Therefore, aluminum alloys have been widely used in modern industrial fields. The key to the widespread application of aluminum and its alloys lies in the welding of aluminum and its alloys, and brazing is the most precise welding method. At the same time, solder paste has important applications in the automated brazing of aluminum and its alloys due to its strong flexibility and wide applicability.
[0003] However, at present, solder pastes used for aluminum and its alloys have the problems of easy sedimentation and low filling rate. In automated applications, too fast sedimentation rate will lead to processing interruption, material waste and other problems, resulting in a significant increase in process costs; while a low filling rate is not conducive to the formation of high-quality welds. Therefore, how to obtain high-filling and high-thixotropic solder paste for brazing aluminum and its alloys has become an urgent problem to be solved. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a high-filling and high-thixotropic AlSi12La0.05 solder paste.
[0005] A first aspect of the present invention provides a highly filled and highly thixotropic AlSi12La0.05 solder paste, comprising the following components and their weight percentages:
[0006] AlSi12La0.05 microspheres, 94.5-94.8wt%;
[0007] Polymethyl methacrylate microspheres, 0.5-1.0wt%;
[0008] 1,3-propylene glycol, 2-2.5 wt%;
[0009] 1,2-Butanediol, 0.5-0.75wt%;
[0010] Octylphenol polyoxyethylene ether (OP-4), 0.5-0.75wt%;
[0011] Nylon acid methyl ester, 0.5-2wt%;
[0012] Among them, the AlSi12La0.05 microspheres include microspheres of the following three particle sizes:
[0013] AlSi12La0.05 microspheres with a particle size of 80 to 100 microns;
[0014] AlSi12La0.05 microspheres with a particle size of 6 to 8 microns;
[0015] AlSi12La0.05 microspheres with a particle size of 1 to 3 microns.
[0016] Optionally, the AlSi12La0.05 microspheres include microspheres with the following particle sizes and weight contents:
[0017] AlSi12La0.05 microspheres with a particle size of 80 to 100 microns, 48 to 48.3 wt%.
[0018] Optionally, the AlSi12La0.05 microspheres further include microspheres with the following particle sizes and weight contents:
[0019] 28.6wt% AlSi12La0.05 microspheres with a particle size of 6 to 8 microns.
[0020] Optionally, the AlSi12La0.05 microspheres include microspheres with the following particle sizes and weight contents:
[0021] 17.9wt% AlSi12La0.05 microspheres with a particle size of 1 to 3 microns.
[0022] Optimally, the AlSi12La0.05 microspheres contain microspheres of the following three particle sizes and weight contents:
[0023] AlSi12La0.05 microspheres with a particle size of 80 to 100 microns, 48 to 48.3 wt%;
[0024] 28.6wt% AlSi12La0.05 microspheres with a particle size of 6 to 8 microns;
[0025] 17.9wt% AlSi12La0.05 microspheres with a particle size of 1 to 3 microns.
[0026] Optionally, the polymethyl methacrylate microspheres have a particle size of 100 to 300 nanometers.
[0027] A second aspect of the present invention provides a method for preparing a high-filling and high-thixotropic AlSi12La0.05 solder paste, comprising the following steps:
[0028] Mix 1,3-propylene glycol, 1,2-butylene glycol, octylphenol polyoxyethylene ether and methyl nylonate in proportion, and stir to mix evenly to obtain a mixed solution 1;
[0029] Add polymethyl methacrylate microspheres in proportion to the obtained mixed solution 1, stir evenly, heat up, stir and keep warm, then continue stirring, and cool to room temperature to obtain a mixture 1; stirring after heating is to maintain uniform and uniform heating during the insulation process;
[0030] AlSi12La0.05 microspheres were added to the obtained mixture 1 in proportion, and at the same time, n-hexane was added, and the mixture was sealed and stirred, and then the sealing state was released, and the temperature was increased, and the temperature was kept and stirred continuously until the n-hexane was completely volatilized, and the mixture was cooled to room temperature to obtain a mixture 2;
[0031] The obtained mixture 2 is subjected to vacuum degassing to obtain a high-filling and high-thixotropic AlSi12La0.05 solder paste.
[0032] Optionally, polymethyl methacrylate microspheres are added to the obtained mixed solution 1 in proportion, wherein the mixture is stirred at a speed of 300 to 500 rpm for 10 minutes, and then the mixture is heated to 70 to 90° C., stirred and kept warm, and then continuously stirred, and cooled to room temperature to obtain a mixture 1. Heating the mixture to 70 to 90° C. can obtain a better slight swelling effect of the polymethyl methacrylate microspheres.
[0033] Optionally, the amount of n-hexane added is 15 wt% of the mixture. In the present invention, n-hexane is a volatile solvent, and n-hexane is added to ensure uniformity of mixing, and the product is obtained after complete volatilization under vacuum decompression.
[0034] Optionally, the sealing is performed to stir and mix, and then the sealing state is released and the temperature is raised to 60-80° C., specifically:
[0035] Cover and seal, stir and mix at a speed of 300 to 500 rpm;
[0036] Then, the lid is opened to release the sealing state, and the temperature is raised to 60-80° C., and the mixture is kept warm and stirred for 2-4 hours until the n-hexane is completely evaporated. The mixture is cooled to room temperature to obtain a second mixture.
[0037] Compared with the prior art, the present invention has at least one of the following beneficial effects:
[0038] The high-filling and high-thixotropic AlSi12La0.05 solder paste of the present invention adopts 2-2.5wt% of 1,3-propylene glycol, 0.5-0.75wt% of 1,2-butylene glycol, 0.5-0.75wt% of octylphenol polyoxyethylene ether (OP-4), and 0.5-2wt% of methyl nylonate, and forms a hydrogen bond network through the compatibility of solvents to improve the thixotropy of the system, that is, the hydrogen bond network is realized by the OH group and O group in the above solvents, and the specific hydrogen bond network density and strength can be realized by optimizing the above ratio. At the same time, the present invention adopts three kinds of AlSi12La0.05 microspheres with different particle sizes to obtain the best filling rate.
[0039] The highly filled and highly thixotropic AlSi12La0.05 solder paste of the present invention achieves paste lubrication and improves the thixotropy of the system through micro-swelling of the surface of polymethyl methacrylate microspheres.
[0040] The highly filled and highly thixotropic AlSi12La0.05 solder paste of the present invention has a stronger polarization ability than conventional AlSi12 microspheres through AlSi12La0.05 microspheres, and is more likely to form charge accumulation on the surface, thereby inhibiting the contact and friction between the microspheres, reducing the viscosity of the system under high filling and obtaining better construction performance.
[0041] The present invention realizes the controllable preparation of high-filling and high-touch AlSi12La0.05 solder paste through the selection and preparation process of components and proportions. The obtained AlSi12La0.05 solder paste realizes a high filling rate of 94.5wt% and a thixotropic index greater than 11. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0043] In the following embodiments, polymethyl methacrylate microspheres, 1,3-propylene glycol, 1,2-butylene glycol, octylphenol polyoxyethylene ether (OP-4), methyl nylonate, and AlSi12La0.05 microspheres with a particle size of 80 to 100 microns, AlSi12La0.05 microspheres with a particle size of 6 to 8 microns, and 17.9 wt% of AlSi12La0.05 microspheres with a particle size of 1 to 3 microns are all commercially available.
[0044] It should be understood that the following embodiments are some preferred embodiments of the present invention, not all embodiments, and the parts not described in detail in the embodiments can be implemented with reference to the prior art.
[0045] Embodiment 1:
[0046] The present embodiment provides a highly filled and highly thixotropic AlSi12La0.05 solder paste, the components and weight contents of which are specifically: 48wt% of AlSi12La0.05 microspheres with a particle size of 80-90 microns, 28.6wt% of AlSi12La0.05 microspheres with a particle size of 6-7 microns, 17.9wt% of AlSi12La0.05 microspheres with a particle size of 1-2 microns, 0.5wt% of polymethyl methacrylate microspheres with a particle size of 100-200 nanometers, 2wt% of 1,3-propylene glycol, 0.5wt% of 1,2-butanediol, 0.5wt% of octylphenol polyoxyethylene ether (OP-4), and 2wt% of methyl nylonate.
[0047] This embodiment further provides a method for preparing the above-mentioned high-filling and high-thixotropic AlSi12La0.05 solder paste, which specifically includes the following steps:
[0048] (1) 1,3-propylene glycol, 1,2-butylene glycol, octylphenol polyoxyethylene ether (OP-4), and methyl nylonate are mixed in proportion, and stirred to obtain a mixed solution 1;
[0049] (2) adding polymethyl methacrylate microspheres in proportion to the mixed solution A obtained in step (1), stirring at a speed of 300 rpm for 10 minutes, heating to 70° C., stirring and keeping the temperature for 20 minutes, then continuing to stir, and cooling to room temperature to obtain a mixture A;
[0050] (3) Add 17.9wt% of AlSi12La0.05 microspheres with a particle size of 80-90 microns, AlSi12La0.05 microspheres with a particle size of 6-7 microns, and AlSi12La0.05 microspheres with a particle size of 1-2 microns to the mixture 1 obtained in step (2) in proportion, and at the same time, add 15wt% of n-hexane to the mixture 1, cover and seal, stir and mix for 30 minutes, and the stirring speed is 300 rpm. Then open the cover to remove the seal, heat to 60°C, keep warm and continue stirring for 2 hours until the n-hexane is completely volatilized, and cool to room temperature to obtain mixture 2;
[0051] (4) The mixture obtained in step (3) is subjected to vacuum degassing to obtain a high-filling and high-thixotropic AlSi12La0.05 solder paste.
[0052] After testing, at 25°C, the viscosity of the solder paste is 510000cp (ASTM D2196, 7# rotor, 10rpm), and the thixotropic index (7# rotor, η 10rpm / η 1rpm ) is 13.3.
[0053] Embodiment 2:
[0054] The present embodiment provides a highly filled and highly thixotropic AlSi12La0.05 solder paste, the components and weight contents of which are as follows: 48.3wt% of AlSi12La0.05 microspheres with a particle size of 90-100 microns, 28.6wt% of AlSi12La0.05 microspheres with a particle size of 7-8 microns, 17.9wt% of AlSi12La0.05 microspheres with a particle size of 2-3 microns, 0.9wt% of polymethyl methacrylate microspheres with a particle size of 200-300 nanometers, 2.4wt% of 1,3-propylene glycol, 0.75wt% of 1,2-butanediol, 0.75wt% of octylphenol polyoxyethylene ether (OP-4), and 2wt% of methyl nylonate.
[0055] This embodiment further provides a method for preparing the above-mentioned high-filling and high-thixotropic AlSi12La0.05 solder paste, which specifically includes the following steps:
[0056] (1) 1,3-propylene glycol, 1,2-butylene glycol, octylphenol polyoxyethylene ether (OP-4), and methyl nylonate are mixed in proportion, and stirred to obtain a mixed solution 1;
[0057] (2) adding polymethyl methacrylate microspheres in proportion to the mixed solution A obtained in step (1), stirring at a speed of 500 rpm for 10 minutes, heating to 90° C., stirring and keeping the temperature for 20 minutes, then continuing to stir, and cooling to room temperature to obtain a mixture A;
[0058] (3) Add 17.9wt% of AlSi12La0.05 microspheres with a particle size of 90-100 microns, AlSi12La0.05 microspheres with a particle size of 7-8 microns, and AlSi12La0.05 microspheres with a particle size of 2-3 microns to the mixture 1 obtained in step (2) in proportion, and at the same time, add 15wt% of n-hexane to the mixture 1, seal and stir for 30 minutes at a stirring speed of 500 rpm. Then open the lid to release the seal, heat to 80°C, keep warm and stir for 3 hours until the n-hexane is completely volatilized, and cool to room temperature to obtain mixture 2;
[0059] (4) vacuum degassing the mixture obtained in step (3) to obtain a high-filling and high-thixotropic AlSi12La0.05 solder paste
[0060] After testing, at 25°C, the viscosity of the solder paste is 430000cp (ASTM D2196, 7# rotor, 10rpm), and the thixotropic index (7# rotor, η 10rpm / η 1rpm ) is 16.7.
[0061] Embodiment 3:
[0062] The present embodiment provides a highly filled and highly thixotropic AlSi12La0.05 solder paste, the components and weight contents of which are as follows: 48.2wt% of AlSi12La0.05 microspheres with a particle size of 85 to 95 microns, 28.6wt% of AlSi12La0.05 microspheres with a particle size of 6.5 to 7.5 microns, 17.9wt% of AlSi12La0.05 microspheres with a particle size of 1.5 to 2.5 microns, 0.75wt% of polymethyl methacrylate microspheres with a particle size of 150 to 250 nanometers, 2.05wt% of 1,3-propylene glycol, 0.6wt% of 1,2-butanediol, 0.65wt% of octylphenol polyoxyethylene ether (OP-4), and 1.25wt% of methyl nylonate.
[0063] This embodiment further provides a method for preparing the above-mentioned high-filling and high-thixotropic AlSi12La0.05 solder paste, comprising the following steps:
[0064] (1) 1,3-propylene glycol, 1,2-butylene glycol, octylphenol polyoxyethylene ether (OP-4), and methyl nylonate are mixed in proportion, and stirred to obtain a mixed solution 1;
[0065] (2) adding polymethyl methacrylate microspheres in proportion to the mixed solution A obtained in step (1), stirring at a speed of 400 rpm for 10 minutes, heating to 80° C., stirring and keeping the temperature for 20 minutes, then continuing to stir, and cooling to room temperature to obtain a mixture A;
[0066] (3) Add 17.9wt% of AlSi12La0.05 microspheres with a particle size of 85-95 microns, AlSi12La0.05 microspheres with a particle size of 6.5-7.5 microns, and AlSi12La0.05 microspheres with a particle size of 1.5-2.5 microns to the mixture 1 obtained in step (2) in proportion, and at the same time, add 15wt% of n-hexane to the mixture 1, seal and stir for 30 minutes at a stirring speed of 400 rpm. Then open the lid to remove the seal, heat to 70°C, keep warm and stir for 4 hours until the n-hexane is completely volatilized, and cool to room temperature to obtain mixture 2;
[0067] (4) The mixture obtained in step (3) is subjected to vacuum degassing to obtain a high-filling and high-thixotropic AlSi12La0.05 solder paste.
[0068] After testing, at 25°C, the viscosity of the solder paste is 470000cp (ASTM D2196, 7# rotor, 10rpm), and the thixotropic index (7# rotor, η 10rpm / η 1rpm ) is 14.8.
[0069] Embodiment 4:
[0070] The present embodiment provides a highly filled and highly thixotropic AlSi12La0.05 solder paste, the components and weight contents of which are as follows: 48wt% of AlSi12La0.05 microspheres with a particle size of 90-100 microns, 28.6wt% of AlSi12La0.05 microspheres with a particle size of 7-8 microns, 17.9wt% of AlSi12La0.05 microspheres with a particle size of 2-3 microns, 1.0wt% of polymethyl methacrylate microspheres with a particle size of 200-300 nanometers, 2.5wt% of 1,3-propylene glycol, 0.75wt% of 1,2-butanediol, 0.75wt% of octylphenol polyoxyethylene ether (OP-4), and 2wt% of methyl nylonate.
[0071] This embodiment further provides a method for preparing the above-mentioned high-filling and high-thixotropic AlSi12La0.05 solder paste, which specifically includes the following steps:
[0072] (1) 1,3-propylene glycol, 1,2-butylene glycol, octylphenol polyoxyethylene ether (OP-4), and methyl nylonate are mixed in proportion, and stirred to obtain a mixed solution 1;
[0073] (2) adding polymethyl methacrylate microspheres in proportion to the mixed solution A obtained in step (1), stirring at a speed of 500 rpm for 10 minutes, heating to 90° C., stirring and keeping the temperature for 20 minutes, then continuing to stir, and cooling to room temperature to obtain a mixture A;
[0074] (3) Add 17.9wt% of AlSi12La0.05 microspheres with a particle size of 90-100 microns, AlSi12La0.05 microspheres with a particle size of 7-8 microns, and AlSi12La0.05 microspheres with a particle size of 2-3 microns to the mixture 1 obtained in step (2) in proportion, and at the same time, add 15wt% of n-hexane to the mixture 1, seal and stir for 30 minutes at a stirring speed of 500 rpm. Then open the lid to remove the seal, heat to 80°C, keep warm and stir for 2 hours until the n-hexane is completely volatilized, and cool to room temperature to obtain mixture 2;
[0075] (4) vacuum degassing the mixture obtained in step (3) to obtain a high-filling and high-thixotropic AlSi12La0.05 solder paste
[0076] After testing, at 25°C, the viscosity of the solder paste is 410000cp (ASTM D2196, 7# rotor, 10rpm), and the thixotropic index (7# rotor, η 10rpm / η 1rpm ) is 16.6.
[0077] Comparative Example 1
[0078] Use commercially available aluminum solder paste (AlSi12)
[0079] The solid content is 83wt% and the viscosity of the solder paste is 560000cp (ASTM D2196, 7# rotor, 10rpm) at 25°C. The thixotropic index (7# rotor, η 10rpm / η 1rpm ) is 3.
[0080] It can be seen from the above-mentioned comparative example 1 that, compared with the existing conventional aluminum solder paste (AlSi12), the AlSi12La0.05 solder paste obtained in the embodiment of the present invention can achieve a high filling rate of 94.5wt% and a thixotropic index greater than 11, which is far superior to the existing conventional aluminum solder paste (AlSi12).
[0081] Comparative Example 2
[0082] 48wt% of AlSi12La0.05 microspheres with a particle size of 70-80 microns, 28.6wt% of AlSi12La0.05 microspheres with a particle size of 9-11 microns, 17.9wt% of AlSi12La0.05 microspheres with a particle size of 4-5 microns, 0.5-1.0wt% of polymethyl methacrylate microspheres with a particle size of 400-500 nanometers, 2wt% of 1,3-propylene glycol, 0.5wt% of 1,2-butylene glycol, 0.5wt% of octylphenol polyoxyethylene ether (OP-4), and 2wt% of methyl nylonate were used. The same preparation process as in Example 1 was adopted, but the mixture could not be formed into a paste in the end, that is, the mixture as a whole presented dry lumps, and the viscosity and thixotropic index could not be tested.
[0083] It can be seen from Comparative Example 2 that the AlSi12La0.05 microspheres in the embodiment of the present invention are more likely to form charge accumulation on the surface, thereby inhibiting the contact and friction between the microspheres, and reducing the viscosity of the system under high filling to obtain better construction performance. At the same time, the AlSi12La0.05 microspheres in the present invention must be microspheres with three specific particle sizes at the same time: AlSi12La0.05 microspheres with a particle size of 80 to 100 microns; AlSi12La0.05 microspheres with a particle size of 6 to 8 microns; AlSi12La0.05 microspheres with a particle size of 1 to 3 microns, in order to obtain the best filling rate. When the three particle sizes of AlSi12La0.05 microspheres do not meet the particle size range defined in the present invention, as shown in the above Comparative Example 2, the effect of the present invention cannot be obtained, and the best filling rate cannot be obtained: the AlSi12La0.05 solder paste obtained in the embodiment of the present invention can achieve a high filling rate of 94.5wt% and a thixotropic index greater than 11.
[0084] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and more embodiments can be obtained by replacing different parameters and proportions. Those skilled in the art can make various deformations or modifications within the scope of the claims, which does not affect the essential content of the present invention.
Claims
1. A high-filling and high-thixotropic AlSi12La0.05 solder paste, characterized in that: Includes the following components and weight percentage: AlSi12La0.05 microspheres, 94.5-94.8wt%; Polymethyl methacrylate microspheres, 0.5-1.0wt%; 1,3-propylene glycol, 2-2.5 wt%; 1,2-Butanediol, 0.5-0.75wt%; Octylphenol polyoxyethylene ether, 0.5-0.75wt%; Nylon acid methyl ester, 0.5-2wt%; Among them, the AlSi12La0.05 microspheres include microspheres of the following three particle sizes: AlSi12La0.05 microspheres with a particle size of 80 to 100 microns; AlSi12La0.05 microspheres with a particle size of 6 to 8 microns; AlSi12La0.05 microspheres with a particle size of 1 to 3 microns.
2. The solder paste according to claim 1, characterized in that: The AlSi12La0.05 microspheres include microspheres with the following particle sizes and weight contents: AlSi12La0.05 microspheres with a particle size of 80 to 100 microns, 48 to 48.3 wt%.
3. The solder paste according to claim 1, characterized in that: The AlSi12La0.05 microspheres also include microspheres with the following particle sizes and weight contents: 28.6wt% AlSi12La0.05 microspheres with a particle size of 6 to 8 microns.
4. The solder paste according to claim 1, characterized in that: The AlSi12La0.05 microspheres include microspheres with the following particle sizes and weight contents: 17.9wt% AlSi12La0.05 microspheres with a particle size of 1 to 3 microns.
5. The solder paste according to claim 1, characterized in that: The AlSi12La0.05 microspheres include microspheres of the following three particle sizes and weight contents: AlSi12La0.05 microspheres with a particle size of 80 to 100 microns, 48 to 48.3 wt%; 28.6wt% AlSi12La0.05 microspheres with a particle size of 6 to 8 microns; 17.9wt% AlSi12La0.05 microspheres with a particle size of 1 to 3 microns.
6. The solder paste according to any one of claims 1 to 5, characterized in that: The particle size of the polymethyl methacrylate microspheres is 100 to 300 nanometers.
7. A method for preparing a high-filling and high-thixotropic AlSi12La0.05 solder paste according to any one of claims 1 to 6, characterized in that The steps include: Mix 1,3-propylene glycol, 1,2-butylene glycol, octylphenol polyoxyethylene ether and methyl nylonate in proportion, and stir to mix evenly to obtain a mixed solution 1; Adding polymethyl methacrylate microspheres in proportion to the obtained mixed solution 1, stirring evenly, heating, stirring and keeping warm, then continuing stirring, and cooling to room temperature to obtain a mixed solution 1; AlSi12La0.05 microspheres were added to the obtained mixture 1 in proportion, and at the same time, n-hexane was added, and the mixture was sealed and stirred, and then the sealing state was released, and the temperature was increased, and the temperature was kept and stirred continuously until the n-hexane was completely volatilized, and the mixture was cooled to room temperature to obtain a mixture 2; The obtained mixture 2 is subjected to vacuum degassing to obtain a high-filling and high-thixotropic AlSi12La0.05 solder paste.
8. The method for preparing the high-filling and high-thixotropic AlSi12La0.05 solder paste according to claim 7, characterized in that: The polymethyl methacrylate microspheres are added to the obtained mixed solution 1 in proportion, wherein the mixture is stirred at a speed of 300 to 500 rpm for 10 to 20 minutes, and then the temperature is raised to 70 to 90° C., stirred and kept warm, and then continuously stirred and cooled to room temperature to obtain a mixture 1.
9. The method for preparing the high-filling and high-thixotropic AlSi12La0.05 solder paste according to claim 7, characterized in that: The amount of n-hexane added is 15 wt % of the mixture.
10. The method for preparing the high-filling and high-thixotropic AlSi12La0.05 solder paste according to claim 7, characterized in that: The sealing is performed to stir and mix, and then the sealing state is released and the temperature is raised to 60-80° C., specifically: Cover and seal, stir and mix at a speed of 300 to 500 rpm; Then, the lid is opened to release the sealing state, and the temperature is raised to 60-80° C., and the mixture is kept warm and stirred for 2-4 hours until the n-hexane is completely evaporated. The mixture is cooled to room temperature to obtain a second mixture.